Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/mc.23406
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling reveals that VNPP433‐3β, the lead next‐generation galeterone analog inhibits prostate cancer stem cells by downregulating epithelial–mesenchymal transition and stem cell markers

Abstract: Cancer stem cells (CSCs) virtually present in all tumors albeit in small numbers are primarily responsible for driving cancer progression, metastasis, drug resistance, and recurrence. Prostate cancer (PCa) is the second most frequent cancer in men worldwide, and castration resistant prostate cancer (CRPC) remains a major challenge despite the tremendous advancements in medicine. Currently, none of the available treatment options are effective in treating CRPC. We earlier reported that VNPP433‐3β, the lead next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…While CTCs are thought to be predominantly biomarkers, CSCs have distinctive features such as high chemo-resistance and may be directly related to metastasis formation [ 87 ]. CSC inhibition may even be applied for targeted therapy in the future [ 88 ]. However, the issue of CSC identification and clinical application was beyond the scope of the present review.…”
Section: Discussionmentioning
confidence: 99%
“…While CTCs are thought to be predominantly biomarkers, CSCs have distinctive features such as high chemo-resistance and may be directly related to metastasis formation [ 87 ]. CSC inhibition may even be applied for targeted therapy in the future [ 88 ]. However, the issue of CSC identification and clinical application was beyond the scope of the present review.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the RNA sequence in this study showed that 18 of 37 genes exhibited dysregulated expression between PCa and lymph node invasion samples, indicating that dysregulated expression levels of different genes played an important role in the lymph node invasion of PCa [ 17 ]. Among these, an androgen receptor (AR) may play an important role for disease progression [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…These cells have distinct biomarkers, and they exhibit high plasticity which allows them to change their phenotypic and functional profile [ 56 ] and they can be identified based on the cell surface molecular markers such as CD44 and CD133 [ 57 ]. Genetic characterization of TICs/CSCs can be performed by investigating the expression of stemness genes, transcription factors, and associated regulatory molecules such as Oct-4, Sox-2, Shh, BMI-1, and Notch-1 [ 57 , 58 ]. These molecular markers collectively help maintain the TICs/CSC pool, which is vital for increased aggressiveness in cancers.…”
Section: Discussionmentioning
confidence: 99%